2020
DOI: 10.1111/bcp.14198
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of fingolimod in patients with relapsing multiple sclerosis: A meta‐analysis

Abstract: Aims The aim of the present meta‐analysis was to evaluate the efficacy and safety of fingolimod in patients with relapsing multiple sclerosis (RMS). Methods PubMed, Embase, the Cochrane Library and http://ClinicalTrials.gov were searched for relevant studies. Two authors independently selected the studies, assessed the risk of bias, and extracted the data. The meta‐analysis was performed in RevMan 5.3 provided by the Cochrane Collaboration. Results Ten studies met the inclusion criteria. In patients with RMS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…With regard to the risk of arrhythmia induced by S1PRM use, our meta-analysis indicated that S1PRMs mainly increased the risk for bradyarrhythmia, a finding that is consistent with the results of several previous studies. One meta-analysis ( 37 ) published in 2020 evaluated the efficacy and safety of fingolimod in 10 RCTs and indicated that fingolimod use was associated with a significantly increased risk of bradycardia (RR, 3.92; 95% CI, 1.30–11.84), a finding that is consistent with our study. However, only bradycardia data were retrieved from that study, as its assessment of the risk of cardiovascular AEs was not comprehensive.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to the risk of arrhythmia induced by S1PRM use, our meta-analysis indicated that S1PRMs mainly increased the risk for bradyarrhythmia, a finding that is consistent with the results of several previous studies. One meta-analysis ( 37 ) published in 2020 evaluated the efficacy and safety of fingolimod in 10 RCTs and indicated that fingolimod use was associated with a significantly increased risk of bradycardia (RR, 3.92; 95% CI, 1.30–11.84), a finding that is consistent with our study. However, only bradycardia data were retrieved from that study, as its assessment of the risk of cardiovascular AEs was not comprehensive.…”
Section: Discussionsupporting
confidence: 91%
“…In these studies, the overall incidence of adverse events (AEs) was counted, and no systematic analysis for specific adverse events (such as infection) was performed. At present, only one study in 2019 evaluated the efficacy and safety of fingolimod using 10 RCTs (27). In that study, bronchitis, nasopharyngitis, sinusitis, and urinary tract infection were considered infection events, and the analysis indicated that fingolimod was associated with a significantly increased risk of bronchitis, which was consistent with our result that fingolimod increased the risk of lower respiratory infection.…”
Section: Comparison With Previous Studiessupporting
confidence: 78%
“…To this end, the total number of relapses of all patients was calculated and divided by the total number of years of drug use to obtain the annual relapse rate of the patients. The obtained value was then divided by the number of patients using each drug in order to obtain the mean relapse rate of each drug (40,41).…”
Section: Effectivenessmentioning
confidence: 99%